Digital Engagement of Local Authorities: From Social Butterflies to Engaged Citizens – A focus on the Nottingham City Council - Komoczi, Viktoria (2014)
The post-2008 global economic recession (Meegan, 2013) and the resultant increase in national debt has led to strict limits being imposed on national public expenditure, following the Government austerity programme of 2010 (Her Majesty's Government, 2010). The reduction has been continuous and fiscal studies forecast that projected income for local authorities is expected to decrease till 2019/20 in general (Local Government Association, 2013b) and for Nottingham City Council in particular. Hence, local authorities are forced to reorganise service provision and look for new ways to decrease expenditure while demand for the most critical council services is rising. This study examines the internet as one area which offers opportunities for reform in response to budget cuts, namely through the delivery of traditional services via 'channel shift' to this medium (Mundy et al., 2011). Therefore, digital engagement is fundamental when public services face severe financial challenges (Local government Association, 2014). Thus, taking greater advantage of Web 2.0 and social media is crucial for a more creative and innovative approach to engaging with citizens and encouraging them to interact with local authorities via online and digital channels. Additionally, this case study provides an in-depth analysis of Nottingham's citizens' preferred method of contacting and communicating with Nottingham City Council. This includes their opinions as well as their evaluation of the customer service on offer. It also benchmarks this social media usage and associate methods of reducing customer contact against the sector leader Manchester City Council and more typical South Derbyshire District Council.